Strategi pemberdayaan berbasis vocational skill pada perempuan miskin di perbatasan Entikong (Indonesia-Malaysia) - Nikodemus Niko (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
This Paper describes the poverty of women at the border of Entikong. The reality of poverty in rural women (border areas) today is still in severe situations. There has been no significance of the welfare development of the community, that in fact there are still many poor women's lives in the country boundary region. It is concluded that the community development program on the border is still loaded with interest and is vulnerable to being politicized by the elites, as a result the development of society is not up to the target. Method of research uses the feminist ethnographic approach as a stand point that research about women comes from a female's own perspective. The data collection techniques are observations, in-depth interviews, documentation studies, and live-in with the community to obtain precise and accurate information. The poverty of women on the border is due to women's limited access to resources. Then, on this paper the empowerment-based vocational skills become a strategic bid in the poverty-alleviation of women at the border.